Salivary Testosterone and Sexual Function and Behavior in Men and Women: Findings from the Third British National Survey of Sexual Attitudes and Lifestyles (Natsal-3). Issue 2 (12th February 2022) - Macdowall, W. G.; Clifton, S.; Palmer, M. J.; Tanton, C.; Copas, A. J.; Lee, D. M.; Mitchell, K. R.; Mercer, C. H.; Sonnenberg, P.; Johnson, A. M.; Wellings, K.
ABSTRACT: Using data from the third British National Survey of Sexual Attitudes and Lifestyles (Natsal-3) we examined associations between salivary testosterone (Sal-T) and sexual function and behavior. Single morning saliva samples were self-collected from a subsample of participants aged 18–74 years and analyzed using mass spectrometry. 1, 599 men and 2, 123 women were included in the analysis (40.6% of those invited to provide a sample). We adjusted for confounders in a stepwise manner: in model 1 we adjusted for age only; model 2 for age, season and relationship status, and model 3 we added BMI and self-reported health. In the fully adjusted models, among men, Sal-T was positively associated with both partnered sex (vaginal sex and concurrent partners) and masturbation. Among women, Sal-T was positively associated with masturbation, the only association with partnered sex was with ever experience of same-sex sex. We found no clear association between Sal-T and sexual function. Our study contributes toward addressing the sparsity of data outside the laboratory on the differences between men and women in the relationship between T and sexual function and behavior. To our knowledge, this is the first population study, among men and women, using a mass spectrometry Sal-T assay to do so.